Regulation of Protein Degradation and Homeostasis by the Cytokine- Inducible Deubiquitinating Enzymes - Kwang-Hyun Baek (International Journal of Immunotherapy and Cancer Research - Peertechz Publications, 2018)
Ubiquitin-proteasome system (UPS) is the major signaling pathway responsible for regulating protein turnover in cells. Deubiquitinating enzymes (DUBs) have an important role in this signaling pathway by eliminating ubiquitins from substrates and inhibiting proteasomal degradation to maintain cellular homeostasis. Based on the published data on cytokine-inducible DUBs including DUB-1, DUB-2, DUB-2A, DUB-1A and DUB-3, they play a pivotal role in the regulation of proliferative and apoptotic processes for immune cells. In this review, I discuss the importance of cytokine-inducible DUBs and the development of new therapeutic targets for these DUBs in immune-related diseases. Ubiquitin-proteasome system (UPS) is the major signaling pathway responsible for regulating protein turnover in cells. Deubiquitinating enzymes (DUBs) have an important role in this signaling pathway by eliminating ubiquitins from substrates and inhibiting proteasomal degradation to maintain cellular homeostasis. Based on the published data on cytokine-inducible DUBs including DUB-1, DUB-2, DUB-2A, DUB-1A and DUB-3, they play a pivotal role in the regulation of proliferative and apoptotic processes for immune cells. In this review, I discuss the importance of cytokine-inducible DUBs and the development of new therapeutic targets for these DUBs in immune-related diseases.